2007
DOI: 10.1007/s10847-007-9404-2
|View full text |Cite
|
Sign up to set email alerts
|

Improved thermal stability of an organic zeolite by fluorination

Abstract: The thermal stability of an organic zeolite material, namely 2,4,6-tris(4-bromo-3,5-difluorphenoxy)-1,3,5-triazin (Br-3,5-DFPOT), was improved by fluorination of 2,4,6-tris(4-bromophenoxy)-1,3,5-triazin (BrPOT). The open pore structure (van der Waals diameter of 10.5 Å ) of the modified zeolite was observed up to 110°C in comparison to 70°C for BrPOT. Nitrogen sorption at low temperature showed a type I isotherm and derived pore volumes thereof are in agreement with structural data. It was observed here that B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…50 However, issues of stability occur often which are limiting the use in many functional applications. Reichenba¨cher et al 51 have recently shown that the selective fluorination of an organic zeolite can improve thermal stability significantly. For the 2,4,6-tris-(4-bromo-3,5-difluorophenoxy)-1,3,5-triazine (26), which is a fluorinated analog of the well known host 2,4,6-tris(4-bromophenoxy)-1,3,5-triazine (27), the open pore structure could be maintained up to a temperature of 110 1C in contrast to only 70 1C for the non-fluorinated parent compound.…”
Section: Inclusion Compoundsmentioning
confidence: 99%
“…50 However, issues of stability occur often which are limiting the use in many functional applications. Reichenba¨cher et al 51 have recently shown that the selective fluorination of an organic zeolite can improve thermal stability significantly. For the 2,4,6-tris-(4-bromo-3,5-difluorophenoxy)-1,3,5-triazine (26), which is a fluorinated analog of the well known host 2,4,6-tris(4-bromophenoxy)-1,3,5-triazine (27), the open pore structure could be maintained up to a temperature of 110 1C in contrast to only 70 1C for the non-fluorinated parent compound.…”
Section: Inclusion Compoundsmentioning
confidence: 99%
“…89 Other dipeptides crystallise with much larger channels, for example, those of L-phenylalanyl-L-phenylalanine are $10 A in diameter, but these have not been shown to possess permanent porosity to date. 123 Other nanoporous molecular crystals with 1-dimensional channels include the unsolvated crystals derived from the natural product 2,2 0 -bis-(formyl-1,6,7-trihydroxy-5-isopropyl-3-methylnaphthalene (Gossypol) 9, which has been shown to adsorb gases (CO 2 ) 93 and vapours (e.g., I 2 and NH 3 ); 92,127 2,4,6-tris(4-bromophenoxy)1,3-triazine (BrPOT) 10, which contains large channels (diameter ¼ 12 A) and adsorbs N 2 at 77 K, although the isotherm has a non-conventional appearance; 95,96 and the 1-D channel-containing inclusion compounds formed by the muchstudied host, 2,6-dimethylbicyclo[3.3.1]nonane-exo-2,exo-6diol, 128 which shows convincing evidence of stability when unsolvated, however, this has not been confirmed by gas adsorption. 129 A number of macrocycles align within crystals to give NMCs with 1-D channels, sometimes termed 'supramolecular nanotubes'.…”
Section: Molecular Nanoporous Crystals With 1-d Channelsmentioning
confidence: 99%
“…162,163 It is often the case that hydrogen bonds help form a two-dimensional lattice, which forms the three dimensional crystal structure through stacking promoted by p-p interactions. 90,101 Also very frequent are p-halogen 65,105,[164][165][166] and full-halogen 102,103 synthons, such as the ones present on the structure shown in Fig. 3.…”
Section: Organic Supramolecular Microporous Solidsmentioning
confidence: 99%